2011
DOI: 10.1172/jci59492
|View full text |Cite
|
Sign up to set email alerts
|

T cell protein tyrosine phosphatase attenuates T cell signaling to maintain tolerance in mice

Abstract: Many autoimmune diseases exhibit familial aggregation, indicating that they have genetic determinants. Single nucleotide polymorphisms in PTPN2, which encodes T cell protein tyrosine phosphatase (TCPTP), have been linked with the development of several autoimmune diseases, including type 1 diabetes and Crohn's disease. In this study, we have identified TCPTP as a key negative regulator of TCR signaling, which might explain the association of PTPN2 SNPs with autoimmune disease. We found that TCPTP dephosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
278
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 192 publications
(306 citation statements)
references
References 76 publications
26
278
2
Order By: Relevance
“…1c). The increase in PTPN2 protein levels in SP thymocytes and naive T cells versus DP thymocytes is consistent with a role in thymic selection 23,26 and the attenuation of T-cell responses to self in the periphery.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…1c). The increase in PTPN2 protein levels in SP thymocytes and naive T cells versus DP thymocytes is consistent with a role in thymic selection 23,26 and the attenuation of T-cell responses to self in the periphery.…”
Section: Resultssupporting
confidence: 67%
“…3a). Previously, we have reported that Lck-Cre;Ptpn2 fl/fl mice develop an effector/memory phenotype as early as 4 weeks of age that progressively develops over time 23 . The Lck-Cre;Ptpn2 fl/fl T cells arising from fast-paced LIP were phenotypically similar to those in 6-week old LckCre;Ptpn2 fl/fl mice, wherein a proportion of the antigenexperienced activated T cells (CD49d hi CD44 hi CD62L lo ) were also IL7Ra lo KLRG1 hi ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations